Defining Quranic Beauty in Divine Harmony: A Stylistic Analysis of Al-Asmā’ Al-Ḥusnā in Surah Al-Baqarah - Murtadho, Muhammad Alfa Choirul; Yahya, Arbi Maulana; Nasrullah, Iklil (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2024)
This article delves into the stylistics features of the Arabic language in the Qur’an, focusing specifically on Surah Al-Baqarah, verses 115 to 130, which highlight Al-Asmā’ al-Ḥusnā, or “the most beautiful names.” These divine names embody the exalted qualities of Allah and provide a pathway to understanding His essence. Through a stylistic lens, the article investigates how various linguistic devices such as metaphors, alliteration, and repetition serve to amplify both the message and the aesthetic appeal of these verses. The analysis reveals that each name not only conveys a unique meaning but also enriches the broader narrative and spiritual framework of Surah Al-Baqarah. With its profound linguistic artistry, the Qur'an encourages readers to contemplate the deeper significance of Allah’s names, fostering a greater connection to their faith and spiritual comprehension. This study seeks to offer fresh insights in Qur'anic scholarship and promote a deeper appreciation of the linguistic beauty inherent in this noble text.